Community conflict, tension and life in new environment: Conflict and its impact on Vadda community in Mahaweli resettlement schemes in Sri Lanka - Epa, Pulsie; Wang Yi Jie; Hu Liang (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2025)
There is a strong relationship between conflict and resettlement, as displaced communities often undergo resettlement following violent conflicts. It is important to consider conflicts during and after the resettlement process and their impact on the community. This study aimed to investigate community disputes in resettlement areas and their impact on daily activities. The qualitative research used an inductive and exploratory approach, applying reflexive thematic analysis. Eighteen respondents were selected through purposive sampling for semi-structured interviews from a resettlement scheme in Hennanigala South, Mahaweli